2006
DOI: 10.1152/ajpregu.00630.2005
|View full text |Cite
|
Sign up to set email alerts
|

ABC drug transporter expression and functional activity in trophoblast-like cell lines and differentiating primary trophoblast

Abstract: drug transporter expression and functional activity in trophoblast-like cell lines and differentiating primary trophoblast.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
130
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(140 citation statements)
references
References 28 publications
9
130
1
Order By: Relevance
“…It must be noted that the present study does not differentiate between the MDR1 (ABCB1) and MDR3 (ABCB4) isoforms of P-gp. Digoxin is a substrate for both efflux transporters, and verapamil inhibits both transporters [37]. Although the MDR3 P-gp homolog may be more abundant in BeWo cells than MDR1, its predominant expression on the basolateral side of human placental trophoblast cells suggests that The transport studies were carried out at 37°C under cell culture conditions with stirring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It must be noted that the present study does not differentiate between the MDR1 (ABCB1) and MDR3 (ABCB4) isoforms of P-gp. Digoxin is a substrate for both efflux transporters, and verapamil inhibits both transporters [37]. Although the MDR3 P-gp homolog may be more abundant in BeWo cells than MDR1, its predominant expression on the basolateral side of human placental trophoblast cells suggests that The transport studies were carried out at 37°C under cell culture conditions with stirring.…”
Section: Discussionmentioning
confidence: 99%
“…PLGA: Poly(lactic-co-glycolic acid). Transport of digoxin-loaded polymeric nanoparticles across BeWo cells Research Article it may efflux substrates in the opposite direction, in other words, toward the fetal side [37]. Therefore, MDR1 may maintain appreciable responsibility in limiting the transplacental transfer of digoxin.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the low oral bioavailability of curcumin, such concentrations are rarely achieved with low to sub nanomolar concentrations typically being observed in plasma, even after oral dosing at 8 g/day for 18 months (Dhillon et al, 2008). BCRP is most abundantly expressed in the apical membrane of placental syncytiotrophoblasts, suggesting that it may play a role in protecting the fetus by impeding xenobiotic penetration across the placental barrier (Jonker et al, 2000;Evseenko et al, 2006). It has been shown that genistein accumulates in Bcrp knockout mice fetuses when genistein was included in the diet of pregnant mice during gestation (Enokizono et al, 2007), implying the involvement of Bcrp in genistein efflux in mouse placenta.…”
Section: Distributionmentioning
confidence: 99%
“…Th e presence of PgP, BCRP, MRP-1 has been confi rmed in the BeWo b30 cells (Atkinson et al 2003, Ceckova et al 2006, Evseenko et al 2006, Milane et al 2009, Mitra and Audus 2010) but inhibitors of PgP and BCRP at a concentration of 50 and 2.5 µM, respectively, showed no eff ect on translocation of PS-NPs across the BeWo b30 cell layers. MK571 (24 µM), an inhibitor of MRP-1, signifi cantly increased the basolateral translocation of positively charged PS-NP by 1.5 fold but did not infl uence the translocation of the negatively charged PS-NPs so in general the translocation of the PS-NPs tested appeared to occur preferentially by passive diff usion.…”
Section: Discussionmentioning
confidence: 95%
“…Th e model consisted of BeWo b30 cells, derived from a human choriocarcinoma, grown on a transwell insert forming a cell layer that separates an apical compartment from a basolateral compartment. When grown on transwell inserts, BeWo b30 cells retain functional adenosine triphosphate binding cassette (ABC) transporters specifi c to the apical and basolateral membranes, such as P-glycoprotein (Pgp), breast cancer resistance protein (BCRP) or multidrug resistance-associated protein 1 (MRP-1) (Utoguchi et al 2000, Atkinson et al 2003, Ceckova et al 2006, Evseenko et al 2006, Milane et al 2009, Mitra et al 2010. Furthermore, these cells express placental diff erentiation markers, such as human chorionic gonadotrophin (HCG) (Takeuchi et al 1990) and the major cytochrome P450 isoforms (CYP1A1 and 1A2) present in placenta (Avery et al 2003).…”
Section: Introductionmentioning
confidence: 99%